Subject-Related As A Significant Demotivating Factor For Non-Muslim Learners Of Arabic As A Foreign Language - Aladdin, Ashinida (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The main objective of this paper is to answer the following questions: a) In subject-related matters, what are the fundamental factors that demotivate non-Muslim learners from learning Arabic? Moreover,; b) How can Arabic language educators encourage Arabic learners to become more motivated to learn the language? An open-ended questionnaire was distributed to 207 respondents in order to investigate the demotivating factors among non-Muslim Arabic learners. In addition, semi-structured interviews with 20 respondents were used to conduct an in-depth investigation of the factors that demotivated Arabic learners regarding subject-related matters. Based on the respondents' elaboration on the issues raised, the researcher explored the underlying patterns of thinking that go beyond the surface level through the analysis of these data obtained using the two types of instruments. According to the study's findings, the main demotivating factor of subject-related matters is the Arabic language. The Arabic language was difficult to learn from the pronunciation, then the writing system and spelling (orthography). And its diacritics after that grammar and vocabulary memorization. In other words, the students are demotivated from learning because of the complexity of the language in general.